Chemical composition of cultivated seaweed ulva clathrata (Roth) C. Agardh - Peña Rodríguez, Alberto; Mawhinney, Thomas P.; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth (Applied Science Publishers, 2011)
Samples of cultivated Ulva clathrata were collected from a medium scale system (MSS, 1.5 1.5 m tank), or from a large scale system (LSS, 0.8 ha earthen pond). MSS samples were dried directly while the LSS sample was washed in freshwater and pressed before drying. Crude protein content ranged 20–26%, essential amino acids accounting for 32–36% of crude protein. The main analysed monosaccharides were rhamnose (36–40%), uronic acids (27–29%), xylose (10–13%) and glucose (10–16%). Some notable variations between MSS and LSS samples were observed for total dietary fibre (26% vs 41%), saturated fatty acids (31% vs 51%), PUFAS (33% vs 13%), carotenoids (358 vs 169 mg kg1 dw) and for Ca (9 vs 19 g kg1 ), Fe (0.6 vs 4.2 g kg1 ), Cu (44 vs 14 mg kg1 ), Zn (93 vs 17 mg kg1 ) and As (2 vs 9 mg kg1 ). The chemical composition of U. clathrata indicates that it has a good potential for its use in human and animal food.